2018
DOI: 10.1128/mcb.00548-17
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 199a-5p Attenuates Retrograde Transport and Protects against Toxin-Induced Inhibition of Protein Biosynthesis

Abstract: Retrograde transport (RT) allows cells the retrieval of receptors and other cellular cargoes to the Golgi contributing to the maintenance of cellular homeostasis. This transport route is also commonly used by several bacterial toxins to exert their deleterious actions on eukaryotic cells. While the retrograde transport process has been well characterized, the contribution of microRNAs (miRNAs) in regulating this cellular transport mechanism remains unknown. Here, we identified that the intronic miRNA family, ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 53 publications
(54 reference statements)
1
11
0
Order By: Relevance
“…The second target, VPS26B, is a component of the core retromer complex. Defects in retromer function attenuate retrograde transport from endosomes to the trans-Golgi network 46,59 : this may induce GA structural and functional alterations as well as inappropriate sorting and recycling activities of endosomes that may lead to increased secretion, as demonstrated for cathepsin-D precursor 60 , and Aβ in Alzheimer's disease 61 .…”
Section: Discussionmentioning
confidence: 99%
“…The second target, VPS26B, is a component of the core retromer complex. Defects in retromer function attenuate retrograde transport from endosomes to the trans-Golgi network 46,59 : this may induce GA structural and functional alterations as well as inappropriate sorting and recycling activities of endosomes that may lead to increased secretion, as demonstrated for cathepsin-D precursor 60 , and Aβ in Alzheimer's disease 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Aranda et al also reported that miR-199a-5p overexpression inhibited the lysosome acidification and reduced autophagosomal degradation, which are a part of the mechanisms for miR-199a-5p to regulate retrograde transport and endolysosomal system in mammalian cells. Their results indicated miR-199a-5p as a negative regulator of autophagy [45]. Yet, the roles of both miR-199a-5p and autophagy in drug-resistant mechanisms of acute myeloid leukemia cells are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Since protein levels were only decreased by 20% whereas currents were almost abolished in the patched cells, we cannot exclude that these miRNAs may alter protein function not only by lowering its expression but also by altering its trafficking and/or the protein surface localization. In agreement with this, it has been shown that miR-199a can strongly influence intracellular trafficking by regulating genes that coordinate retrograde transport and endocytosis [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 61%